PENGEMBANGAN MEDIA SUKAMO BERBASIS DEEP LEARNING UNTUK MENINGKATKAN MEMBACA PERMULAAN SISWA SD - Aisyah Nur Afifah Maulidiyyah; Setya Yuwana Sudikan; Wahyu Sukartiningsih; Nurul Istiq'faroh; M. Bambang Edi Siswanto; Hendratno Hendratno (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The low level of early reading skills among elementary school students remains a challenge in early literacy instruction. This study aims to develop the Montessori Syllable (SUKAMO) teaching material using a valid, practical, and effective Deep Learning approach to improve the early reading skills of first-grade elementary school students. The novelty of this study lies in the integration of Montessori principles with the characteristics of Deep Learning through manipulative, exploratory, collaborative, and reflective activities, thereby creating a conscious, meaningful, and enjoyable learning experience. The study employed the Research and Development (R&D) method using a modified 4-D development model consisting of three stages: define, design, and develop. The “disseminate” stage was not implemented due to time and budget constraints. The study combined quantitative and qualitative data through expert validation, observation, interviews, questionnaires, and early reading proficiency tests. The research subjects consisted of 64 first-grade students at Al Islah Elementary School in Surabaya, divided into an experimental class and a control class, each comprising 32 students. The results showed that the SUKAMO teaching material met validity criteria based on assessments by subject matter experts, media experts, and language experts. The material was also deemed practical based on teachers’ feedback that it was highly practical, positive student responses, and students’ active engagement during lessons. The results of the Analysis of Covariance (ANCOVA) demonstrated that the use of SUKAMO had a significant effect on students' beginning reading skills after controlling for their initial reading ability. The improvement in beginning reading skills achieved by the experimental group was greater than that of the control group, indicating that integrating Montessori-based media with the Deep Learning approach effectively enhanced students' ability to recognize letters, read syllables, and read simple words. Therefore, the SUKAMO media is considered appropriate for use in beginning reading instruction at the elementary school level and contributes to the development of Montessori-based literacy media that supports student-centered, mindful, meaningful, and joyful learning. ABSTRAK Rendahnya kemampuan membaca permulaan siswa sekolah dasar masih menjadi tantangan dalam pembelajaran literasi awal. Penelitian ini bertujuan mengembangkan media Suku Kata Montessori (SUKAMO) melalui pendekatan Pembelajaran Mendalam (Deep Learning) yang valid, praktis, dan efektif untuk meningkatkan kemampuan membaca permulaan siswa kelas I sekolah dasar. Kebaruan penelitian ini terletak pada integrasi prinsip Montessori dengan karakteristik Pembelajaran Mendalam melalui aktivitas manipulatif, eksploratif, kolaboratif, dan reflektif sehingga menciptakan pengalaman belajar yang berkesadaran, bermakna, dan menggembirakan. Penelitian menggunakan metode Research and Development (R&D) dengan model pengembangan 4-D yang dimodifikasi menjadi tiga tahap, yaitu define, design, dan develop. Tahap disseminate tidak dilaksanakan karena keterbatasan waktu dan biaya penelitian. Penelitian mengombinasikan data kuantitatif dan kualitatif melalui validasi ahli, observasi, wawancara, angket, serta tes kemampuan membaca permulaan. Subjek penelitian terdiri atas 64 siswa kelas I SD Al Islah Surabaya yang terbagi ke dalam kelas eksperimen dan kelas kontrol, masing-masing berjumlah 32 siswa. Hasil penelitian menunjukkan bahwa media SUKAMO memenuhi kriteria valid berdasarkan penilaian ahli materi, ahli media, dan ahli bahasa. Media juga dinyatakan praktis berdasarkan respons guru yang sangat praktis, respons siswa yang positif, serta aktivitas belajar siswa yang aktif selama pembelajaran. Hasil uji Analysis of Covariance (ANCOVA) menunjukkan bahwa penggunaan media SUKAMO memberikan pengaruh yang signifikan terhadap kemampuan membaca permulaan setelah kemampuan awal siswa dikendalikan. Peningkatan kemampuan membaca pada kelas eksperimen lebih tinggi dibandingkan kelas kontrol, yang menunjukkan bahwa integrasi media Montessori dengan Pembelajaran Mendalam mampu mengoptimalkan kemampuan mengenal huruf, membaca suku kata, dan membaca kata sederhana. Dengan demikian, media SUKAMO layak digunakan sebagai media pembelajaran membaca permulaan di sekolah dasar serta berkontribusi dalam pengembangan media literasi yang mendukung pembelajaran berpusat pada siswa, berkesadaran, bermakna, dan menggembirakan.